Agent-based simulation : (Springer, 2005)
Agent-based modeling/simulation is an emerging field that uses bottom-up and experimental analysis in the social sciences. Selected research from that presented at the Third International Workshop on Agent-Based Approaches in Economic and Social Complex Systems 2004, held in May 2004 in Kyoto, Japan, is included in this book. The aim of the workshop was to employ the bottom-up approach to social and economic problems by modeling, simulation, and analysis using a software agent. This research area is an emerging interdisciplinary field among the social sciences and computer science, attracting broad attention because it introduces a simulation-based experimental approach to problems that are becoming increasingly complex in an era of globalization and innovation in information technology. The state-of-the-art research and findings presented in this book will be indispensable tools for anyone involved in this rapidly growing discipline.